The asymmetric impact of macroeconomic variables on Islamic bank home financing in Indonesia - Faaza Fakhrunnas; Mohammad Abdul Matin Chowdhury; MB Hendrie Anto (Jurnal Ekonomi dan Keuangan Islam, 2023)
Purpose – The study investigates the performance of non-performing financing (NPF) in the housing sector concerning the asymmetric influence of macroeconomic conditions.